The Influence of Anode/Cathode Capacity Ratio on Cycle Life and Potential Variations of Lithium-Ion Capacitors. Issue 12 (24th July 2019) - Naderi, R.; Shellikeri, A.; Hagen, M.; Cao, W.; Zheng, J. P.
Abstract : Lithium-ion capacitors (LICs) incorporate the fundamental features of intercalation battery materials and double-layer capacitor materials, to bring together the desirable combination of high energy and power densities, long cycle life and materials stability. But, the presence of battery materials in anode also contribute toward LIC's long-term capacity fade, based on its extent of utilization. This work studies the importance of anode to cathode capacity ratio, and its influence on the electrodes potential variation and capacity decay behaviors. In a LIC system based on activated carbon (AC) and hard carbon (HC), we show that increasing the HC:AC capacity ratio from 1.1 to 3, boosts the capacity retention of the LIC by 10% after 2, 000 cycles at 1C rate, and by 28% after 20, 000 cycles at 60C rate. During the intermittent EIS and 3-electrode galvanostatic tests at 0.25C rate, lower anode over-potential is observed for LIC with larger anode to cathode capacity ratio. Pointing toward a reduced charge transfer and Warburg diffusion resistances, based on the potential at which the anode was operating. The 1C and 60C rates long term tests and intermittent tests at 0.25C rate were in agreement that LIC with larger HC:AC capacity ratio had a better electrochemical performance.